Kemampuan tenaga pendidik dalam memanfaatkan pembelajaran berbasis e-learning - Abdul Hakim; Nurhikmah H (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The Activities of Community Partnership Program(PKM) carried out in Makassar. The partnership problems are:1) The changes of Information and CommunicationTechnology (ICT) that affect an education, 2) the ability ofeducators in using ICT, especially the use of an internet inlearning is still lack, utilizing some learning programs basedon e-learning primarily, and 3) the availability of internetinvarious of places can be used freely, both of at school andcampus. The results obtained from the training activities wereattended by 27 teaching staff both teachers and lecturers,showing that, 1) the implementation of e-learning basedlearning went smoothly because it was supported by availablefacilities, 2) The selection of marking moodle programs basedon needs and facilities available, further activities of PKM arecarried out directly to provide examples and mentoringparticipants. The facilitator in understanding and compiling elearningbased learning, and 3) All participants produceavailable e-learning products.